2018
DOI: 10.1002/adma.201804684
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Li3PS4 Solid‐State Electrolyte Protection Layers for Superior Long‐Life and High‐Rate Lithium‐Metal Anodes

Abstract: A thin and adjustable Li3PS4 (LPS) solid‐state electrolyte protection layer on the surface of Li is proposed to address the dynamic plating/stripping process of Li metal. The LPS interlayer is formed by an in situ and self‐limiting reaction between P4S16 and Li in N‐methyl‐2‐pyrrolidone. By increasing the concentration of P4S16, the thickness of the LPS layer can be adjusted up to 60 nm. Due to the high ionic conductivity and low electrochemical activity of Li3PS4, the intimate protection layer of LPS can not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
107
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(112 citation statements)
references
References 52 publications
4
107
0
1
Order By: Relevance
“…In recent years,e xtensive efforts have been devoted to restraining dendrite growth on Li metal anodes.These include applying three-dimensional Li hosts, [6] protective coating on Li metal, [7] employing dendrite-free separators or interlayers, [8] stabilizing the SEI by optimizing liquid electrolytes, [9] salts [10] or electrolyte additives, [11] and replacing liquid electrolytes with inorganic solid electrolytes or polymer electrolytes, [12] etc.A mong the above-mentioned methods,t he application of polymer electrolytes is of particular interest due to their unique merits such as flexible processability,low flammability,h igh tolerance to mechanical deformation, and better electrode/electrolyte interfacial properties compared with inorganic solid electrolytes. [13] To date,t wo kinds of polymer electrolytes are widely employed in the research of Li metal batteries,that is,all-solid-state single-ion conducting polymer electrolytes (SIPEs) [14] and crosslinked gel polymer electrolytes (CGPEs).…”
mentioning
confidence: 99%
“…In recent years,e xtensive efforts have been devoted to restraining dendrite growth on Li metal anodes.These include applying three-dimensional Li hosts, [6] protective coating on Li metal, [7] employing dendrite-free separators or interlayers, [8] stabilizing the SEI by optimizing liquid electrolytes, [9] salts [10] or electrolyte additives, [11] and replacing liquid electrolytes with inorganic solid electrolytes or polymer electrolytes, [12] etc.A mong the above-mentioned methods,t he application of polymer electrolytes is of particular interest due to their unique merits such as flexible processability,low flammability,h igh tolerance to mechanical deformation, and better electrode/electrolyte interfacial properties compared with inorganic solid electrolytes. [13] To date,t wo kinds of polymer electrolytes are widely employed in the research of Li metal batteries,that is,all-solid-state single-ion conducting polymer electrolytes (SIPEs) [14] and crosslinked gel polymer electrolytes (CGPEs).…”
mentioning
confidence: 99%
“…Compared to the pristine Li, Raman spectrum of the modified Li demonstrated three typical peaks between 300 and 600 cm −1 . Formation of Li 3 PS 4 was supported by the band at 420 cm −1 [41,43,44] . Band between 350 and 410 cm −1 indicated that some other Li x P y S z type compounds such as Li 4 P 2 S 7 and Li 4 P 2 S 6 formed [44,[47][48][49][50][51] .…”
Section: The Characterization Of Morphology and Compositionmentioning
confidence: 92%
“…4 (a) and (b) shows the P 2 p and S 2 p XPS spectra of the modified Li foil. The broad peak in P 2 p signal was fitted into two peaks at 134.1 eV and 133.3 eV, corresponding to P 4 S 10 and PS 4 3 − , respectively [41,44,45] . Accordingly, the sulfur signals at 164.5 eV and 163.3 eV were assigned to P-S-P bridging bond and P = S double bond in P 4 S 10 [45] .…”
Section: The Characterization Of Morphology and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many approaches have been taken to address the above-mentioned issues in order to improve Li plating/ stripping [16][17][18]. Optimization of the electrolyte is a widely used approach to improve SEI formation and facilitate uniform deposition of Li metal [19], including using new electrolytes [20][21][22][23], highly concentrated electrolytes [24][25][26][27] and/or new additives [28][29][30]. Another efficient method is the modification of the interface between Li metal and electrolyte by applying an artificial layer of materials such as organosulfide, polyvinyl alco-hol, highly elastic polyrotaxane, LiF/h-BN or Li 2 S 6 /P 2 S 5 [31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%